STRUKTUR GERAK TARI TUPAI JONJANG DI KANAGARIAN LUMPO KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN - Kartika Masria Sari; Afifah Asriati; Darmawati Darmawati (FBS Universitas Negeri Padang, 2013)
Abstract This article was aimed at describing the movement structure of Tupai Jonjang dance in Kanagarian Lumpo Kecamatan Empat Jurai Kabupaten Pesisir Selatan. This was a qualitive research that used descriptive method. The object of the research was Tupai Jonjang dance. The data was collected through observation, interview and documentation. In analyzing the data, the researcher analyzed the structure of the hierarchical relationship. The result of the research revealed that (1) the structure of the basic element relationship in Tupai Jonjang dance movement consisted of the combination of the movement of head, body, hand and legs. All of these movements formed a motive. (2) the structure of hierarchical relationship consisted of 28 motive, 12 pharases, 5 sentences and a group. The structure of the paradigmatic relationship was the most dominant among others on the level of motive, pharase and sentence. Kata kunci: struktur, gerak, tari Tupai Jonjang, deskripsi.